Pola Baru Bisnis Masa Depan - FX Supriyono (Center for Economic Studies Universitas Katolik Parahyangan, 1999)
The paper will discuss social responsibility that is related to business. The term 'social responsibility' refers to the responsibility of managers or organizations in carrying out their socially approved missions, to be responsive to, to be congruent with and to interact and live with the forces and elements of their social environment. Social responsibility was still perceived as the burden for almost all of the business society in Indonesia. This perception was then followed by business malpractices that created disadvantages for the society as a whole. Recently, as people were not passive anymore, the business society can no longer do what they want to do without social considerations. Business is not merely a matter of economics. The existence of businesses should provide the society with welfare. This new paradigm is a new challenge for Indonesian businesses today and in the future.